Introduction to modern analysis - Kantorovitz, Shmuel; Viselter, Ami (New York : Oxfrod University Press, 2022)
"Introduction Modern Analysis aims to bring to the reader a comprehensive account from undergraduate subjects in measure theory and basic functional analysis to advanced topics studied in graduate courses. Among the topics we cover are measure theory, basic functional analysis, single operator theory, spectral theory (of bounded and unbounded operators), semigroups of operators, Banach algebras, C*-algebras and their standard constructions, von Neumann algebras, probability and mathematical statistics, and partial differential equations. The book can serve motivated students interested in these areas for self-study, as well as professional researchers as a reference"--
Includes bibliography and index